Ethanol Sensitization during Adolescence or Adulthood Induces Different Patterns of Ethanol Consumption without Affecting Ethanol Metabolism - Carrara-Nascimento, Priscila F.; Hoffmann, Lucas B.; Contó, Marcos B.; Marcourakis, Tania; Camarini, Rosana (Frontiers in Behavioral Neuroscience, 2017)
In previous study, we demonstrated that ethanol preexposure may increase ethanol consumption in both adolescent and adult mice, in a two-bottle choice model. We now questioned if ethanol exposure during adolescence results in changes of consumption pattern using a three-bottle choice procedure, considering drinking-in-the-dark and alcohol deprivation effect as strategies for ethanol consumption escalation. We also analyzed aldehyde dehydrogenase (ALDH) activity as a measurement of ethanol metabolism. Adolescent and adult Swiss mice were treated with saline (SAL) or 2.0 g/kg ethanol (EtOH) during 15 days (groups: Adolescent-SAL, Adolescent-EtOH, Adult-SAL and Adult-EtOH). Five days after the last injection, mice were exposed to the three-bottle choice protocol using sucrose fading procedure (4% + sucrose vs. 8%–15% ethanol + sucrose vs. water + sucrose) for 2 h during the dark phase. Sucrose was faded out from 8% to 0%. The protocol was composed of a 6-week acquisition period, followed by four withdrawals and reexposures. Both adolescent and adult mice exhibited ethanol behavioral sensitization, although the magnitude of sensitization in adolescents was lower than in adults. Adolescent-EtOH displayed an escalation of 4% ethanol consumption during acquisition that was not observed in Adult-EtOH. Moreover, Adult-EtOH consumed less 4% ethanol throughout all the experiment and less 15% ethanol in the last reexposure period than Adolescent-EtOH. ALDH activity varied with age, in which older mice showed higher ALDH than younger ones. Ethanol pretreatment or the pattern of consumption did not have influence on ALDH activity. Our data suggest that ethanol pretreatment during adolescence but not adulthood may influence the pattern of ethanol consumption toward an escalation in ethanol consumption at low dose, without exerting an impact on ALDH activity.